Social Media Use Profile of Farmers in Haryana - Ayush Mishra,; Jogender Singh, Joginder Singh Malik,; Abhilash Singh Maurya, (Indian Journal of Extension Education, 2022)
Social media are digital networks that are used to share and discuss user generated information - opinion, video, audio, and multimedia spreading far and wide even in remote areas of the country and has changed the way farmers communicate and interact. This study was conducted in 2021, with an objective to understand to understand the use of social media by farmers and to analyze its relationship with economic profile characteristic. The data were collected personally from Hisar and Sonipat districts of Haryana, with a sample size of 200 respondents comprising 25 farmers from eight villages through a structured interview schedule. Findings revealed that 69.00 per cent of the respondents were in the medium category of social media use. Garrett's ranking analysis revealed that watching videos was the most preferred purpose of social media use among farmers followed by chatting/ connecting with peers. Also, YouTube was found to be most preferred social media followed by WhatsApp and Facebook. Further, education, family income, cosmopoliteness-localiteness, social participation, extension contact and extension participation showed a positive relationship with social media use while age had negative relationship. Also, regression analysis showed that the eleven personal variables selected for the study could explain 53.30 percent variation in social media use.